2017
DOI: 10.1002/pdi.2089
|View full text |Cite
|
Sign up to set email alerts
|

Early postpartum glycaemic assessment in patients with gestational diabetes

Abstract: Uptake of postpartum glycaemic assessment in women with gestational diabetes (GDM) has been shown to be low, with six weeks postpartum testing (as recommended by the UK National Institute for Health and Care Excellence) inconvenient for new mothers who prioritise their new baby over their own health at this time. As pregnancy‐related insulin resistance returns to pre‐pregnancy levels immediately after placental delivery, we hypothesised that early postpartum fasting blood glucose testing, while the mother is l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 24 publications
0
7
1
Order By: Relevance
“…The results of this study showed a significant, temporary improvement in maternal fasting glucose in all subcategories of glycaemia 24–72 hours following delivery. In contrast to similar published work, early post-delivery glucose testing was not found to be a feasible alternative to the standard of care 4-12-week postpartum visit in women with HFDP within our population group [ 14 , 17 – 21 ]. The study failed to identify high risk individuals and did not demonstrate that in-hospital fasting glucose could help to direct resources to those most in need of surveillance.…”
Section: Discussioncontrasting
confidence: 91%
See 2 more Smart Citations
“…The results of this study showed a significant, temporary improvement in maternal fasting glucose in all subcategories of glycaemia 24–72 hours following delivery. In contrast to similar published work, early post-delivery glucose testing was not found to be a feasible alternative to the standard of care 4-12-week postpartum visit in women with HFDP within our population group [ 14 , 17 – 21 ]. The study failed to identify high risk individuals and did not demonstrate that in-hospital fasting glucose could help to direct resources to those most in need of surveillance.…”
Section: Discussioncontrasting
confidence: 91%
“…Published studies pertaining to early post-delivery glucose assessment in GDM women as an alternative to the 4-12 week OGTT were mostly favourable. Curtis et al, (2017) explored this novel approach in 118 GDM women in the UK [14] . Similar to the findings of our study 110/115 women (95.6%) had a normal FPG at t1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 Finally, Curtis et al showed that early post-partum glycaemic assessment with a FPG performed before hospital discharge was associated with a total uptake of 94.9%, and is therefore an effective strategy to increase screening uptake in women with previous GDM. 30 While this is a relatively new strategy for post-partum glucose screening, the authors suggested that these results would not be much different to those of the 6-week post-partum testing recommended by NICE. 30 The subsequent follow-up of women with previous GDM should still remain a priority, while the validity of this strategy needs to be further evaluated by studies on larger populations.…”
Section: Screening Uptakementioning
confidence: 97%
“…30 While this is a relatively new strategy for post-partum glucose screening, the authors suggested that these results would not be much different to those of the 6-week post-partum testing recommended by NICE. 30 The subsequent follow-up of women with previous GDM should still remain a priority, while the validity of this strategy needs to be further evaluated by studies on larger populations. 30 Women with a history of GDM are high-risk individuals who require a consistent, patient-centred approach and management.…”
Section: Screening Uptakementioning
confidence: 97%